Current sector control for a three-phase three-level PFC rectifier - O. Tubburee (2018)
© 2015 Korean Institute of Power Electronics. In this paper, a control algorithm of a three-phase three-level power factor correction (PFC) rectifier, using a mathematical analysis of two-level space vector modulation (SVM), is presented. The proposed control scheme was developed, in order to generate the duty cycle signals for each switching device based on the discontinuous space vector modulation (DSVM) method. For this proposal it is not essential to determine the direction of line currents and sector of vectors, only to recognize the angle of the input reference voltage. Furthermore, the number of commutations of switches and switching losses are reduced due to the DSVM method. Simulation and calculation results can confirm the feasibility of the control algorithm and performance of the proposed rectifier.